Effect of curing, wax application and packaging on collar breakdown and quality in stored ’Nagpur’ mandarin (Citrus reticulata) - LADANIYA, M S; SONKAR, R K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted in 1995 Mrig crop season (March-May) to find out the role of curing or hardening, manual and mechanical wax (stay-fresh high-shine wax @ 2.5%) application and vented polyethylene liner on collar breakdown disorder, various losses and quality characteristic of ’Nagpur’ mandarin (Citrus reticulata Blanco) fruit under ambient storage conditions. The collar breakdown disorder appeared as sunken, dry and brown-coloured tissues of collar due to injury and drying. Curing or hardening for 30 hr after harvest added to water loss and aggravated collar breakdown. The finding also indicated need to try softer washer brushes. The collar breakdown and decay level were very low in non-cured fruits manually and mechanically waxed and packed in polyethylene with non-significant difference between the 2 treatments. polyethylene liner significantly minimized the water loss. Curing, mechanical waxing and packing without polyethylene had cumulative effect on water loss and incidence of collar breakdown. Decay was more in non-waxed fiuit pncked in polyethylene. Carbendazim (2 000 ppm) in wax minimized tile decay due to Diplodia natalendsis P. Evans. Maximum retention of natural freshness, firmness, total soluble solids: acid ratio, flavour and shine of ’Nagpur’ mandarin was recorded when non-cured fruits were manually or mechanically waxed and stored in polyethylene-lined boxes up to 21 days at ambient conditions.